Design and analysis of a novel variable stiffness actuator based on parallel-assembled-folded serial leaf springs. (17th September 2017) - Bi, S. S.; Liu, C.; Zhao, H. Z.; Wang, Y. L.
Abstract: Variable stiffness actuator (VSA) can significantly improve the dynamic performance of robots and ensure safety in human robot interaction. In this paper, a novel structure-controlled VSA which achieves a lower minimal stiffness while the size and load capacity remain unchanged is introduced. Stiffness variation is implemented by changing the effective length of parallel-assembled-folded serial leaf springs presented in this paper, which makes the adjustment of stiffness easier and driven by an independent motor. A modified analytical model of joint stiffness is built, which takes the gap between leaf springs and rollers into consideration. Experiments prove that the modified model is more accurate comparing with the ideal model which ignores the gap. Further analyses show that the gap can even make serious impacts on leaf spring-based structure-controlled VSA in other performances such as deformability and energy capacity. Graphical Abstract: